Teachers need analysis: Development of the Urban Heat Island module based on a contextual approach - Siti Azizah Susilawati; Mohd Hairy Ibrahim; Nor Kalsum binti Mohd Isa; Muhammad Musiyam; Rita Noviani (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2023)
Since the nineteenth century, scientists have studied the Urban Heat Island (UHI). The negative effects of UHI could be mitigated with the help of interdisciplinary studies, but none have been performed so far. UHI research in schools has some holes that could seriously hinder students' grasp of climate change. The purpose of this research is to ascertain whether or not the Urban Heat Island module is necessary for enhancing students' understanding of climate change in the classroom. The Greater Solo Area Region's 72 geographic teachers were chosen at random for this study. Preliminary data on teachers' familiarity with UHI in the Greater Solo Area shows that, on average, they know very little about UHI. About 47 percent of the teachers surveyed had no understanding at all of UHI, while the remaining 25 percent had a moderate amount of knowledge, seven percent had high understanding, and three percent had very high understanding. Results from a test given to educators in both the suburbs and the city corroborated these observations. All teachers agreed that the UHI enrichment module created using a contextual approach was necessary as a supplementary medium for climate change material, as indicated by the results of the teacher needs assessment tests.